Body composition and physical fitness in elite water polo athletes - Di Vincenzo, O.; Marra, M.; Di Gregorio, A.; Caldara, A.; De Lorenzo, A.; Scalfi, L. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
Elite water polo athletes participate in several high-intensity bouts undergoing heavy training programs. An optimal athletic performance is a result of many factors, including changes in body composition (BC) during the sport season. Aim of this study was to evaluate the relation between BC and physical fitness in an elite water polo team national first league. Ten water polo men athletes (17-26 years) were studied. Data were collected during the regular season of the 2018/2019 Italian Men's Water Polo First League. BIA parameters, resistance (R) and phase angle (PhA) were measured at 50 kHz and BC was evaluated. The physical fitness tests performed were hand grip strength (HGS), long jump (LJ) and squat jump (SJ). Our study showed that LJ, SJ and HGS were positively related to FFM (Fat-Free Mass) and LJ was also positively related to whole-body phase angle but not to upper- or lower-limbs. This preliminary study underlines a close correlation between physical fitness and FFM.